2013
DOI: 10.1111/ecc.12058
|View full text |Cite
|
Sign up to set email alerts
|

The experiences of gay and bisexual men diagnosed with prostate cancer: results from an online focus group

Abstract: Research concerning gay and bisexual men diagnosed with prostate cancer is sparse. An online focus group was conducted over a 4-week period with participants responding to a range of discussion questions concerning their experiences following a prostate cancer diagnosis. Emerging themes were identified and consensus reached. A summary of each of the themes was produced which the coders agreed conveyed the essence of the online discussion. All men who took part in the online focus group reported that prostate c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
217
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(223 citation statements)
references
References 21 publications
2
217
1
Order By: Relevance
“…Lack of participant consensus, a common focus group phenomena, also contributes to data richness helping researchers to identify areas of agreement and controversy within group norms (Kitzinger, 1994). The unique ability of focus group discussions to tap into social interactions has popularized it as a qualitative method in many health care studies, given that health care encounters and delivery are interactive processes (Asbury, 1995; Thomas, Wootten, & Robinson, 2013; Watson, Peacock, & Jones, 2006). …”
Section: Online Focus Groups: History Methodological Considerationsmentioning
confidence: 99%
“…Lack of participant consensus, a common focus group phenomena, also contributes to data richness helping researchers to identify areas of agreement and controversy within group norms (Kitzinger, 1994). The unique ability of focus group discussions to tap into social interactions has popularized it as a qualitative method in many health care studies, given that health care encounters and delivery are interactive processes (Asbury, 1995; Thomas, Wootten, & Robinson, 2013; Watson, Peacock, & Jones, 2006). …”
Section: Online Focus Groups: History Methodological Considerationsmentioning
confidence: 99%
“…The ways in which LGB individuals are affected by cancer and how they cope were discussed within several papers, indicating many sexual minority attitudes are common with heterosexual cancer survivors, but sexual minorities may report poorer health [24,[26][27][28]53,54].…”
Section: Coping and Wellbeingmentioning
confidence: 99%
“…An Australian study examined the experiences of ten SMM diagnosed with prostate cancer, the results indicated that some participants adopted a sense of empowerment regarding their cancer journey whilst others felt isolated as a result of their treatments [24]. The data was gathered through online focus groups.…”
Section: Coping and Wellbeingmentioning
confidence: 99%
“…An advantage of online applications of NGT and of group discussions in general is that they offer anonymity, which has been found to stimulate disclosure in sensitive topics (Tates et al, 2009, Stover & Goodman, 2012. Importantly, the online form can enable researchers to gain access to groups that are difficult to engage via others research methods, in particular young people and vulnerable groups (Stewart & Williams, 2005;Yu et al 2011;Thomas et al 2013). For researchers, the online application saves (travel) expenses and time for transcribing data since the data are already in writing (Tates et al, 2009).…”
Section: Data Collection and Analysismentioning
confidence: 99%